Disease scoring systems for oral lichen planus; a critical appraisal - Wang, Jing (Med Oral Patol Oral Cir Bucal, 2015)
The aim of the present study has been to critically review 22 disease scoring systems (DSSs) on oral lichen planus (OLP) that have been reported in the literature during the past decades. Although the presently available DSSs may all have some merit, particularly for research purposes, the diversity of both the objective and subjective parameters used in these systems and the lack of acceptance of one of these systems for uniform use, there is a need for an international, authorized consensus meeting on this subject. Because of the natural course of OLP characterized by remissions and exacerbations and also due to the varying distribution pattern and the varying clinical types, e.g. reticular and erosive, the relevance of a DSS based on morphologic parameters is somewhat questionable. Instead, one may consider to only look for a quality of life scoring system adapted for use in OLP patients. Key words:Oral lichen planus, disease scoring system, classification.